The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/febs.13420
|View full text |Cite
|
Sign up to set email alerts
|

Dps from Deinococcus radiodurans: oligomeric forms of Dps1 with distinct cellular functions and Dps2 involved in metal storage

Abstract: The DNA binding proteins from starved cells from Deinococcus radiodurans, Dps1-DR2263 and Dps2-DRB0092, have a common overall structure of hollow spherical dodecamers. Their involvement in the homeostasis of intracellular metal and DNA protection was addressed. Our results show that DrDps proteins are able to oxidize ferrous to ferric iron by oxygen or hydrogen peroxide. The iron stored inside the hollow sphere cavity is fully released. Furthermore, these proteins are able to store and release manganese, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 85 publications
2
43
0
Order By: Relevance
“…Additionally, the upregulation of a putative metal efflux pump (SOA0154) in S. oneidensis, proposed to be involved in the detoxification of UVA-irradiated cells (Qiu et al, 2005) supports the hypothesis that 79 times below normal dose rates of radiation is perceived as a stress. Interestingly, D. radiodurans cultures exhibited the down regulation of dps, known to contribute to DNA protection from ROS through the maintenance of metal homeostasis (Santos et al, 2015), in agreement with previous findings on the reduced transcription of this gene in the presence of H 2 O 2 (Chen et al, 2008); and of gapdH, an essential component of glucose metabolism during glycolysis. After first documenting growth inhibition and the lack of stress-gene response in D. radiodurans to the absence of normal levels of radiation (Castillo et al, 2015), in the data reported here, we added qPCR assays for various previously reported stress-related genes, including homologs to those responsive in S. oneidensis, of which two were regulated, suggesting that D. radiodurans' response to this unusual environmental cue might be derived from different gene regulation events.…”
Section: A Biological Role For Background Ionizing Radiation?supporting
confidence: 91%
“…Additionally, the upregulation of a putative metal efflux pump (SOA0154) in S. oneidensis, proposed to be involved in the detoxification of UVA-irradiated cells (Qiu et al, 2005) supports the hypothesis that 79 times below normal dose rates of radiation is perceived as a stress. Interestingly, D. radiodurans cultures exhibited the down regulation of dps, known to contribute to DNA protection from ROS through the maintenance of metal homeostasis (Santos et al, 2015), in agreement with previous findings on the reduced transcription of this gene in the presence of H 2 O 2 (Chen et al, 2008); and of gapdH, an essential component of glucose metabolism during glycolysis. After first documenting growth inhibition and the lack of stress-gene response in D. radiodurans to the absence of normal levels of radiation (Castillo et al, 2015), in the data reported here, we added qPCR assays for various previously reported stress-related genes, including homologs to those responsive in S. oneidensis, of which two were regulated, suggesting that D. radiodurans' response to this unusual environmental cue might be derived from different gene regulation events.…”
Section: A Biological Role For Background Ionizing Radiation?supporting
confidence: 91%
“…However, the Dps2 could biosynthesize AgNPs rather than AuNPs ( Figures 8C and D and S4B). The different roles of the Dps2 in reducing Au(III) and Ag(I) might be due to the following: first, the Dps2, which functions as a sequester of intracellular Fe 2+ ion and stores iron ions in the form of Fe 3+ , 53 could not adsorb or interact with the trivalent Au ions; however, it did reduce the monovalent Ag ions; second, Dps2 only contains three tryptophan and six tyrosine molecules that have the ability of donating electrons from their NH or OH groups (Table S2) 54,55 and thus could not have enough potential to synthesize the AuNPs, considering the relative higher reduction potential of gold (E =0.799 V). 56,57 Thus, the metal NP's biosynthetic ability with different proteins might be determined by their composition or reducing capability.…”
Section: Synthesis Of Aunps and Agnps By Selective Proteinsmentioning
confidence: 99%
“…Our earlier results on the NpDps1-3 showed that none of these three proteins could catalyze the O 2 -mediated oxidation reaction, while H 2 O 2 acted as a good oxidant. To investigate whether NpDps4 exhibits similar oxidant preferences as the canonical NpDps we used kinetic absorption spectroscopy to monitor the oxidation of Fe 2+ to Fe 3+ from which an increase in the absorbance at 310 nm arises [4,34] (Fig 5).…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic absorption spectroscopy following the wavelength at 310 nm to monitor the formation of Fe 3+ species [4,34]. A.…”
Section: Resultsmentioning
confidence: 99%